Coastal catch transects as a tool for studying global fisheries. Issue 3 (25th February 2013) - Watson, Reg; Pauly, Daniel
Abstract We present a new, intuitive approach for the representation of fisheries catches within profiles perpendicular to coast of the Exclusive Economic Zones (EEZ) of countries, or of Large Marine Ecosystems (LME). These 'catch transects' show where catch is extracted in the water column and near the sea bottom on plots of log‐bathymetry versus log‐distance offshore and thus allow for representation of the catch density of pelagic and benthic fisheries. Hence, they also allow direct visual comparison of the intensity of fishing through time and space. The California Current, North Sea and the South China Sea LMEs and the EEZs of Australia, Canada, Chile, China, India and Thailand are presented as examples, revealing the general intensification and extension of fishing offshore and into the depths over the decades from the 1950s. Catch transects reveal how these trends have accelerated in some areas, but surprisingly have reversed themselves in some others. It is proposed that these catch transects will be particularly useful for communicating the results of large‐scale fisheries studies to a wide spectrum of groups ranging from the fishing industry to the general public.